Optimum throwing and jumping angles in athletics - Linthorne, N. P. (1999)
To achieve maximum performance in the throwing and jumping events, the athlete must project the implement or body with the optimum combination of projection speed and projection angle. Many biomechanists have noticed that the projection angles used by athletes differ from the optimum angles predicted by the mechanics of projectile motion. For example, the predicted optimum release angle in the shot put is about 42° , whereas world-class athletes use release angles of around 37° . Studies were conducted that show that the discrepancies arise, not because of errors in the athletes` techniques, but because the calculations of the optimum projection angles do not account for the biomechanics of the projection phase of the event. Measurements were taken of the release speed, release height, and release angle of five male collegiate shot-putters throwing at a wide range of release angles. For all five athletes, the release speed decreased with release angle, and the release height increased with release angle. When these relations were combined with the equation for the range of a projectile, the calculated optimum release angles were in good agreement with the athletes` competition release angles. Each athlete had his or her own specific optimum release angle because of inter-individual differences in the rate of decrease of release speed with release angle. A similar study was performed with a world-class athlete jumping at a wide range of take-off angles. Again, the take-off speed decreased with take-off angle, and the take-off height increased with take-off angle. The optimum take-off angles in the long jump and high jump were calculated by combining the biomechanical relations of the take-off with the equations for the range and flight height of a projectile. The calculated optimum take-off angles for both the long jump (22°) and high jump (45°) were in good agreement with the athlete`s competition take-off angles. The method of combining the biomechanics of the projection phase with the mechanics of projectile motion may also be used to calculate the optimum release angle in the discus throw, hammer throw, and javelin throw. However, the calculations for these events are more complex because of aerodynamic effects in the flight phase of the implement. To be able to provide correct biomechanical advice to an athlete, a sports biomechanist must have a theoretical model that includes all of the mechanics and biomechanics relevant to the event. This study showed that to correctly calculate the optimum projection angle in throwing and jumping, the investigator must account for the biomechanics of the projection phase of the event, as well as the mechanics of the flight phase.